Graphene-based catalytic membranes for water treatment – A review - Pedrosa, Marta; Figueiredo, José L.; Silva, Adrián M.T. (Journal of environmental chemical engineering, 2021)
Progress on the development and performance of graphene-based catalytic membranes for water treatment applications, particularly using advanced oxidation technologies (AOTs), is the subject of this review. A detailed search on Scopus database provided 79 studies concerning catalytic membranes made up of graphene derivatives for water treatment applications, namely for the effective removal of aqueous organic contaminants by photocatalysis, electrocatalysis and persulfate/peroxymonosulfate activation catalysis. The main goal of this review is the analysis of the existing studies dealing with graphene-derived catalytic membranes for water treatment, in particular assessing information of: i) membrane fabrication approaches, ii) target pollutants, and iii) graphene production methods. From a critical point of view, 60 studies (76%) evaluated the membrane performance towards the degradation of dyes, which are easily removed by most of the typical catalytic oxidation reactions. Most publications refer to the use of Hummers’-derived graphene analogues (59 studies, or ~75%) and vacuum filtration (33 studies, or 44%) as the chosen catalytic carbon material and membrane fabrication procedure, respectively. Fifty-six studies (71%) evaluated membrane performance under filtration mode, while the other 23 reports (29%) focused on batch mode of operation, which is far from the reality of a full-scale membrane filtration process. Moreover, various authors proposed the generation of reactive oxygen species (ROS), such as HO•, O2•−, among others, in the removal of several contaminants. Additional research is still needed, concerning cost-analysis of the processes, the possible reactivity of graphene-based membranes with ROS (i.e. understanding how to preserve long-term membrane stability) and using real water matrices. [Display omitted] •Graphene derived catalytic membranes are effective water treatment options.•Photocatalysis, PS/PMS activation and electrocatalysis are the most employed AOTs.•Membrane fabrication, target pollutants and graphene production methods are discussed.•Research using real water matrices is needed.•Possible membrane reactivity with generated ROS should be investigated.